How Are Under Ice Phytoplankton Related to Sea Ice in the Southern Ocean?. Issue 21 (9th November 2021) - Bisson, K. M.; Cael, B. B.
Abstract: Little is known about Southern Ocean under‐ice phytoplankton, despite their suspected potential—ice and stratification conditions permitting—to produce blooms. We use a distributional approach to ask how Southern Ocean sea ice and under‐ice phytoplankton characteristics are related, circumventing the dearth of co‐located ice and phytoplankton data. We leverage all available Argo float profiles, together with freeboard (height of sea ice above sea level) and lead (ice fractures yielding open water) data from ICESat‐2, to describe co‐variations over time. We calculate moments of the probability distributions of maximum chlorophyll, particulate backscatter, the depths of these maxima, freeboard, and ice thickness. Argo moments correlate significantly with freeboard variance, lead fraction, and mixed layer depth, implying that sea ice dynamics drive plankton by modulating how much light they receive. We discuss ecological implications in the context of data limitations and advocate for diagnostic models and field studies to test additional processes influencing under‐ice phytoplankton. Plain Language Summary: While sea ice undoubtedly influences under ice phytoplankton to some extent, little is known about under‐ice phytoplankton in the Southern Ocean due to the paucity of field data. In the absence of plankton and ice measurements made at the same time and place, we can make inferences about the potential links between the two by comparing the average and variability of many measurements made within the same region. We do so with satellite‐based measurements of freeboard (the thickness of sea ice above the water level) versus measurements made from profiling floats that measure plankton characteristics. We find that the average freeboard is unrelated to these plankton measures but that when freeboard is more variable, phytoplankton stocks tend to be higher and occur at shallower depths. These nonintuitive results encapsulate how plankton communities' response to light is complex, and suggest that plankton may respond positively to a more variable light field. Key Points: Freeboard (ICESat‐2) and under‐ice plankton profiles (biogeochemical Argo floats) are compared via their probability distributions Freeboard variance, but not mean, is correlated to mean backscattering and chlorophyll maxima and the depths of these Freeboard may influence plankton via modulation of light penetration, mixed layer depth, and sea ice leads